Sisi Positif Taqlîd dalam Sejarah Perkembangan Hukum Islam - Mawardi, Ahmad Imam (ISLAMICA: Jurnal Studi Keislaman, 2011)
The main problem that this paper is interested in dealing with is the notion of taqlid, the English translation of which being a blind acceptance. Taqlid is the opposite of Ijtihad, the intellectual exercise to draw certain legal rules from their sources. Muslims over centuries believed that taqlid in legal matters is not allowed, and that the door of Ijtihad has never been closed, as some Western scholars would emphatically argue. The paper nonetheless maintains that taqlid does take place in a major part of Islamic legal history. It has become unavoidable for Muslims to accept blindly âdue to some reasons- the legal views of the earlier scholars and jurists. But the paper also argues that to accept without question the views of the authoritative scholars in legal matters is not always bad. The paper tries to show that there are âdue to some conditions- positive things in committing Taqlid. To show this, the paper would attempt to scrutinize the historical facts in which Muslims do benefit from doing Taqlid. It means also that, Ijtihad is not always good for Muslims. By presenting some findings -the paper will argue- that in some cases, Muslims should abandon independent intellectual exercise and resort to blind acceptance if in doing so would bring benefit for them.